2003
DOI: 10.1111/j.1582-4934.2003.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 modulates cellular growth and promotes tumorigenesis

Abstract: Cyclooxygenase (COX) -2 and the prostaglandins resulting from its enzymatic activity have been shown to play a role in modulating cell growth and development of human neoplasia. Evidence includes a direct relationship between COX-2 expression and cancer incidence in humans and animal models, increased tumorigenesis after genetic manipulation of COX-2, and significant anti-tumor properties of non-steroidal anti-inflammatory drugs in animal models and in some human cancers. Recent data showed that COX-2 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 125 publications
(127 reference statements)
1
99
1
2
Order By: Relevance
“…Cox-2 has been shown to contribute constitutively to the physiologic regulation and development in these highly differentiated organ systems. 17 Recent data showed that Cox-2 and the prostaglandins resulting from its enzymatic activation are involved in the control of cellular growth, angiogenesis, apoptosis, and development of neoplasia. Selective Cox-2 inhibitor attenuated the retinal angiogenesis that accompanies retinopathy of prematurity, and normal retinal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox-2 has been shown to contribute constitutively to the physiologic regulation and development in these highly differentiated organ systems. 17 Recent data showed that Cox-2 and the prostaglandins resulting from its enzymatic activation are involved in the control of cellular growth, angiogenesis, apoptosis, and development of neoplasia. Selective Cox-2 inhibitor attenuated the retinal angiogenesis that accompanies retinopathy of prematurity, and normal retinal development.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Several studies showed that Cox-2 functions as a survival factor by protecting cells from apoptosis. [17][18][19][20][21] Overexpression of Mcl-1, a member of the Bcl-2 family, 22 delays apoptosis by a broad array of agents. 18,21,[23][24][25][26] Bad is a proapoptotic member of the Bcl-2 gene family that promotes apoptosis by binding to and inhibiting functions of antiapoptotic proteins Bcl-2 and Bcl-xL.…”
mentioning
confidence: 99%
“…Three major classes of enzymes are involved in generating eicosanoids: cyclooxygenases (COX), which produce prostaglandins, lipoxygenases, which generate leukotrienes and hydroxyeicosatetraenoic acids, and cytochrome P450 enzymes which mediate the synthesis of 19-and 20-hydroxyeicosatetraenoic acids (HETEs), epoxyeicosatrienoic acids (EETs) and diHETEs (see Fig 1 for a summary of eicosanoid metabolism) (Funk, 2001). In the skin, COX-derived metabolites are known to control many aspects of inflammation, cell growth control, apoptosis and tumor development (Trifan and Hia, 2003). Two key COX enzymes have been extensively characterized, COX-1, a constitutive enzyme, and COX-2, an enzyme induced by many irritants and inflammatory agents (Fitzpatrick, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are two isoforms of the cyclooxygenase enzyme: cyclooxygenase-1 (Cox-1), which is a housekeeping protein that is constitutively expressed in most human tissues, and cyclooxygenase-2, (Cox-2), which is typically not expressed unless the cell is stimulated by growth factors, tumor promoters, cytokines, or hormones [20,21]. An up-regulation of Cox-2 expression has been demonstrated in various cancer types including cancers of the esophagus [22,23], stomach [24,25], colon [26][27][28], and bladder [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%